Films based on cassava starch reinforced with soybean hulls or microcrystalline cellulose from soybean hulls. (June 2019) - Merci, Aline; Marim, Renan Guilherme; Urbano, Alexandre; Mali, Suzana
Graphical abstract: Highlights: Starch films reinforced with soybean hulls (SH) or microcrystalline cellulose (MCC). SH and MCC addition improved processability of extruded starch-glycerol films. SH and MCC added at 2.5% decreased films solubility and water vapor permeability. Addition of 2.5% MCC improved films flexibility. Addition of 5% fiber (SH or MCC) resulted in more brittle and hygroscopic films. Abstract: The objectives of this work were to produce films based on cassava starch reinforced with soybean hulls (SH) or microcrystalline cellulose (MCC) obtained from SH by reactive extrusion. The SH and MCC were used at different concentrations (0, 2.5, and 5.0% w/w), and glycerol (25–30 % w/w) was used as a plasticizer to obtain films by extrusion. The addition of 2.5% SH and MCC led to films with lower solubility, water vapor permeability and hygroscopicity than pure starch film, and incorporation of 2.5% MCC improved the film flexibility. The addition of 5% fiber (SH or MCC) resulted in more brittle and hygroscopic films. The incorporation of 2.5% SH and MCC generated films with better performance than that of pure starch ones, and this combination could be a strategy to obtain extruded films with a fully renewable source of polymeric matrix composed mainly of starch.